Ergonomic Risk Assessment for Refuse Collectors at Chitungwiza Municipality in Zimbabwe - Norman Gumbo; Jonathan Chisvo; Taremba Chirigo (Trends in Ecological and Indoor Environmental Engineering)
Background: Waste-related activities such as collecting and segregating mixed waste are associated with a number of health hazards. These hazards include microbiological exposure associated with the collection of putrefying material, chemicals from the waste itself and from its decomposition, as well as exhaust fumes from trucks, noise, extreme temperatures, ultraviolet radiation, and more. Occupational risks for waste collection workers include increased environmental and workload-related injuries (sprains and fractures associated with lifting, carrying, pushing/dragging heavy objects and awkward positions), what causes diseases of the musculoskeletal system.